Hepatocellular carcinoma and non-Hodgkin's lymphoma: the roles of HIV, hepatitis C infection, and alcohol abuse. - McGinnis, Kathleen A; Fultz, Shawn L; Skanderson, Melissa; Conigliaro, Joseph; Bryant, Kendall; Justice, Amy C (Journal of clinical oncology : official journal of the American Society of Clinical Oncology, 2006)
To explore the relationship of HIV, hepatitis C (HCV), and alcohol abuse/dependence to risk for hepatocellular carcinoma and non-Hodgkin's lymphoma (NHL).
Keywords: Adult; Alcoholism; Carcinoma, Hepatocellular; Hepatitis C; HIV Infections; Humans; Incidence; Liver Neoplasms; Lymphoma, Non-Hodgkin; Male; Middle Aged; Retrospective Studies; Risk Assessment; Risk Factors; United States; Veterans